Sweeney Todd: Adapting a Victorian Urban Legend. - Martín-González, Juan José (Universidad de Málaga, 2013)
This chapter is aimed at examining two neo-Victorian adaptations of the legend of Sweeney Todd: Stephen Sondheim’s Sweeney Todd. The Demon Barber of Fleet Street. A Musical Thriller (1979) and Tim Burton’s Sweeney Todd, the Demon Barber of Fleet Street (2007). Firstly, taking the analytical tenets of Adaptation theories as a point of departure, I will consider the medium-specific features of theatre and cinema that come out in the play and the film referred above respectively. Secondly, I will look into how violence is portrayed in each adaptation and I will peruse the social-political resonances of the legend in general by tracing briefly its adaptation evolution from the nineteenth century up to nowadays.
Keywords: Adaptaciones cinematográficas; Folklore urbano; Sweeney Todd; Stephen Sondheim; Tim Burton; Urban legends; Adaptation